TASK1 and TASK3 in orexin neuron of lateral hypothalamus contribute to respiratory chemoreflex by projecting to nucleus tractus solitarius. Issue 5 (4th April 2021) - Wang, Xia; Guan, Ruijuan; Zhao, Xiaomei; Chen, Jun; Zhu, Danian; Shen, Linlin; Song, Nana
Abstract: TWIK‐related acid‐sensitive potassium channels (TASKs)‐like current was recorded in orexin neurons in the lateral hypothalamus (LH), which are essential in respiratory chemoreflex. However, the specific mechanism responsible for the pH‐sensitivity remains elusive. Thus, we hypothesized that TASKs contribute to respiratory chemoreflex. In the present study, we found that TASK1 and TASK3 were expressed in orexin neurons. Blocking TASKs or microinjecting acid artificial cerebrospinal fluid (ACSF) in the LH stimulated breathing. In contrast, alkaline ACSF inhibited breathing, which was attenuated by blocking TASK1. Damage of orexin neurons attenuated the stimulatory effect on respiration caused by microinjection of acid ACSF (at a pH of 6.5) or TASKs antagonists. The orexinA‐positive fiber and orexin type 1 receptor (OX1R) neurons were located in the nucleus tractus solitarius (NTS). The exciting effect of acidosis in the LH on respiration was inhibited by blocking OX1R of the NTS. Taken together, we conclude that orexin neurons sense the extracellular pH change through TASKs and regulate respiration by projecting to the NTS.